Pelatihan kompetensi literasi digital bagi guru bahasa inggris berbasis e-learning moodle - Nadiah Ma'mun; Siti Mariam (Rengganis Jurnal Pengabdian Masyarakat, 2021)
In the era of the COVID-19 epidemic that is currently sweeping the entire world, the teaching and learning process at every level of education must continue. Various learning methods and tools are used both offline and online. Online learning is still limited and must adhere to strict health protocols. Meanwhile, online learning is a solution to this situation. Many online media can be used, for example, Google Classroom, WA group, Zoom, Cisco Webex, Google Duo, and others. This community service aims to help teachers improve their skills in using the Moodle application.. It’s currently considered the most fully-featured application for online (distance) learning. During the activation process, starting from the socialization process to training, the teachers were very interested in this activity, this was evidenced by the number of invited participants who all came. Participants attended the training from beginning to end, participants actively participated in the training and there were many questions and complaints submitted by the Teacher. After the training, participants implemented the use of the Moodle application in learning English online. Some teachers practice making teaching materials, online discussions, quizzes, and assignments while teaching, while asking questions and motivating students.